2010
DOI: 10.1007/s00018-010-0278-x
|View full text |Cite
|
Sign up to set email alerts
|

P2X7, NMDA and BDNF receptors converge on GSK3 phosphorylation and cooperate to promote survival in cerebellar granule neurons

Abstract: Glycogen synthase kinase-3 (GSK3) is a key player in the regulation of neuronal survival. Herein, we report evidence of an interaction between P2X7 receptors with NMDA and BDNF receptors at the level of GSK3 signalling and neuroprotection. The activation of these receptors in granule neurons led to a sustained pattern of GSK3 phosphorylation that was mainly PKC-dependent. BDNF was the most potent at inducing GSK3 phosphorylation, which was also dependent on PI3K. The P2X7 agonist, BzATP, exhibited additive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 35 publications
4
46
0
Order By: Relevance
“…When purified neuronal cultures were used, ATP and BzATP induced a consistent increase in cell viability, suggesting that activation of P2X7 receptors in retinal neurons in the absence of glial cells might be neuroprotective. These observations are in good agreement with recent findings showing that activation of P2X7 receptors is neuroprotective against PI3K/Akt inhibition in purified cultures of rat cerebellar granule cells [23,24] and the discrepancies between our findings and those mentioned before could be due to differences in the methodological conditions used. Zhang et al observed significant levels of ganglion cell death when freshly dissociated retinal cultures were incubated with BzATP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When purified neuronal cultures were used, ATP and BzATP induced a consistent increase in cell viability, suggesting that activation of P2X7 receptors in retinal neurons in the absence of glial cells might be neuroprotective. These observations are in good agreement with recent findings showing that activation of P2X7 receptors is neuroprotective against PI3K/Akt inhibition in purified cultures of rat cerebellar granule cells [23,24] and the discrepancies between our findings and those mentioned before could be due to differences in the methodological conditions used. Zhang et al observed significant levels of ganglion cell death when freshly dissociated retinal cultures were incubated with BzATP.…”
Section: Discussionsupporting
confidence: 93%
“…Both P2X3 and P2X7 receptors were shown to inhibit axonal growth and branching of developing motor axons [19], cultured hippocampal neurons [21], and neuroblastoma cells [22]. Moreover, activation of P2X7 receptors was shown to promote the survival of cerebellar granule cells [23,24], but the death of cultured striatum-derived neural progenitors [25], a conflicting observation that now can be explained by the recent detection and characterization of P2X7 receptor splice variants with distinct functional properties [26,27]. While P2X7A receptor induces cell permeabilization and death, the truncated P2X7B receptor that lacks the carboxy-terminal induces cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…The speed with which β-catenin is activated suggests that P2X7 regulates the stability of β-catenin as opposed to its gene expression at early time points. In this regard, we showed that P2X7 activation in osteoblast-like cells rapidly inhibits GSK3β in a PKCdependent manner in agreement with previous findings in cerebellar granule neurons [13,22]. Interestingly, the PTH-PTH 1 receptor complex has also been shown to facilitate canonical Wnt signaling through inhibition of GSK3β in osteoblast-like SaOS-2 cells [28].…”
Section: P2x7 Potentiates the Wnt/β-catenin Pathwaysupporting
confidence: 91%
“…In cerebellar granule neurons, activation of P2X7 has been shown to inhibit GSK3β through mechanisms dependent on protein kinase C (PKC) [13,22]. Previous work from our lab has demonstrated that stimulation of P2X7 in osteoblasts activates Ca 2+ signaling and the phosphatidylinositol 3-kinase (PI3K) pathway [17,23].…”
Section: Activation Of P2x7 Increases Inhibitory Phosphorylation Of Gmentioning
confidence: 99%
“…In contrast to their accepted contribution to neurodegeneration, neuroprotective actions of P2X7 receptors have also been reported (Skaper et al, 2010). In rat cerebellar granule neurons, P2X7 receptors activate a survival pathway alternative to that of the classic neurotrophic factors, depending on protein kinase C activation but converging on glycogen synthase kinase-3 inhibition to promote neuronal survival (Ortega et al, 2010). P2X7 receptors could also be involved in neuronal development.…”
Section: Introductionmentioning
confidence: 99%